Contemporary concepts of small town development - Farelnik, Eliza (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The paradigms of sustainable development and knowledge and innovation-based economy (smart growth) are among the most important signposts for the development of contemporary towns, cities and regions. The growing competitiveness of cities and the high variation and complexity of the urban environment necessitate the search for such a model of a city that will enable its dynamic development in the economic, social and spatial spheres. The implemented development model determines the town’s ability to face the current challenges, such as population changes, increasing and diverse needs of the city’s users, limited natural resources which therefore require protection, a shift in the paradigm of local economy towards circular economy, thereby improving the town’s ability to deal with crisis (urban resilience). As a consequence, there is a growing number of smart cities as well as cities which have adopted another dominant development concept, such as green cities, slow cities. Aim: Purpose of the article is to discuss and compare some of these concepts, namely smart city, slow city, green city (and selected hybrid models), which can be applied in designing a policy for the development of small towns in Poland. Results: The diverse and increasingly varied conditions underlying the development of small towns mean that a local development policy should have a more reactive and scenario-like character. The process of evolution of the existing approaches can be observed, resulting in the hybridization of the development models, where new concepts arise by combining the assumptions of several approaches, for example a smart green city, etc. This process can be seen as the manifestation of improving the level of urban resilience to crises, which increases the chance of small towns to adapt to new conditions.